Telenursing thru SMS Its effect on knowledge and adherence to proper diet and physical activity - Pangan, Ina Cristina; Pangilinan, Gianne Alyssa; Pangilinan, Milcah; Pangilinan, Recah; Pangilinan, Romina; Par, Carl Justine; Paragas, Erickson (2011)
This study aims to develop and implement telenursing intervention program to increase the knowledge and adherence to proper diet and physical activity for the prevention of weight related diseases such as Hypertension Type II Diabetes mellitus, and cardiovasular diseases among overweight college students aged 18-25 years old. 24 college students undergone the DeFit It! Program. They have a body mass index (BMI) between 25.00-25.99 kg/m^3. Subjects in the experimental group were subjected to telenursing by receiving 4 daily short messaging service (SMS) for 21 days regarding health education and proper diet and physical activity, and reminders to follow the DeFit it! Program. There is a significant increase in the knowledge of telenursing users when compared to nontelenursing users. There is a significant decrease in the BMI of the nontelenursing users which may be attributed to their low diet adherence scores since they ate in less than recommended mount of diet.
Keywords: Short messaging service; Physical activity; Diet